Breast‐Specific Gamma Imaging Influences Surgical Management in Patients with Breast Cancer. Issue 5 (14th July 2013) - Edwards, Claire; Williams, Stephanie; McSwain, Anita P.; Damle, Sameer; Rapelyea, Jocelyn A.; Downs, Kara; Torrente, Jessica; Sambamurty, Anita; Brem, Rachel F; Teal, Christine B.
Abstract Breast‐specific gamma imaging (BSGI) is a physiologic breast imaging modality that provides more sensitive detection of breast lesions than mammography or ultrasound, and appears to have greater specificity than breast MRI. The purpose of this study was to evaluate how often BSGI changed surgical management in patients with breast cancer. Charts were reviewed from 218 consecutive eligible patients who had preoperative evaluation with BSGI or MRI before surgery for breast cancer from January 2008 to May 2010. Patients who were initially considered eligible for breast‐conserving therapy (BCT) were evaluated to determine how many ultimately had mastectomies. Patients who underwent mastectomy because of personal choice or ineligibility for BCT were excluded. Management was changed to mastectomy in 11.9% of those who had BSGI and 28.9% of those who had MRI. Review of pathology demonstrated that all patients who underwent mastectomies were not candidates for breast conservation. 15.4% of patients who underwent BCT based on BSGI findings required a single re‐excision due to positive surgical margins. 14.4% required mastectomy. In the MRI group, 18.8% required a single re‐excision, and 6.3% required mastectomy. Evaluation with BSGI changed management to mastectomy in a substantial proportion of patients believed to be eligible for BCT following standard imaging. BSGI is effective in evaluation of extent of disease in patients with breast cancer, and is comparable to MRI in terms of its influence on surgical management.